LincRNA-p21 suppresses glutamine catabolism and bladder cancer cell growth through inhibiting glutaminase expression. Issue 4 (12th April 2019) - Zhou, Qun; Zhan, Hengji; Lin, Fan; Liu, Yuhan; Yang, Kang; Gao, Qunjun; Ding, Mengting; Liu, Yuchen; Huang, Weiren; Cai, Zhiming
Abstract : Long intergenic non-coding RNA p21 (lincRNA-p21) is down-regulated in some solid tumors. Glutamine catabolism plays an important role in cancer development. However, the role of lincRNA-p21 and its association with glutamine catabolism remain unknown in bladder cancer (BC). In the present study, we investigated the involvement of lincRNA-p21 and glutamine catabolism in BC cell growth and found that ectopic linRNA-p21 expression reduced the proliferation and growth of BIU87 and 5637 cells. Opposite results were observed in lincRNA-p21 silenced J82 and T24 cells. The expression of glutaminase (GLS), intracellular level of glutamate and α-Ketoglutarate (α-KG) were negatively regulated by lincRNA-p21. GLS overexpression reversed the suppressive function of lincRNA-p21 on BC cell growth and proliferation. In contrast, GLS reduction by siRNA blunted the viability of lincRNA-p21 lowly expressed BC cells. Furthermore, lincRNA-p21 and GLS abundance dictated the sensitivity of BC cells to bis-2-(5-phenylacetamido-1, 2, 4-thiadiazol-2-yl)ethyl sulfide (BPTES) treatment. Importantly, reduced lincRNA-p21 expression and increased GLS mRNA level were observed in BC tissues compared with the normal tissues. Our results demonstrate that lincRNA-p21 suppresses the BC cell growth through inhibiting GLS and glutamine catabolism. Targeting this cascade may be a promising treatment strategy for BC patients.